2019
DOI: 10.21608/ajar.2019.59744
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and regional variations of five heavy metals in water, sediments and fishes inhabiting Lake Qarun, Egypt

Abstract: The study was conducted during the period from October 2015 to September 2016 to investigate the accumulation of five heavy metals in three fish species (Tilapia zillii, Solea solea and Mugil cephalus) inhabiting lake Qarun, Egypt. Water, sediments and fish samples were collected from six sites cover eastern, middle and western sectors of the lake during the four studied seasons. The results indicated that, summer time showed the highest pH, salinity, biological oxygen demand and nitrates concentration, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…On the other hand, the central area had more zinc (Zn), cobalt (Co), rubidium (Rb), and strontium (Sr), which matches what El-Kady and others found in 2019, where they also saw that metals were more concentrated in the eastern part of the lake, especially near El-Batts drain (El-Kady et al, 2019). In all three parts of Qaroun Lake -east, middle, and west -there was a lot of iron (Fe), even more than recorded (Elwasify, 2019); it shows that the sediment has more iron than usual, which probably comes from the land around the lake and is causing pollution (Bantan et al, 2020; Ejaz et al, 2020). When we looked at the results from this study and compared them to earlier ones about Qaroun Lake, we saw that there was more manganese (Mn), copper (Cu), and zinc (Zn) than what those previous studies found by (Elwasify, 2019) Regarding the content of organic matter in the current study, it was like those obtained by El-Zeiny et al…”
Section: Heavy Metals Distributionsmentioning
confidence: 98%
“…On the other hand, the central area had more zinc (Zn), cobalt (Co), rubidium (Rb), and strontium (Sr), which matches what El-Kady and others found in 2019, where they also saw that metals were more concentrated in the eastern part of the lake, especially near El-Batts drain (El-Kady et al, 2019). In all three parts of Qaroun Lake -east, middle, and west -there was a lot of iron (Fe), even more than recorded (Elwasify, 2019); it shows that the sediment has more iron than usual, which probably comes from the land around the lake and is causing pollution (Bantan et al, 2020; Ejaz et al, 2020). When we looked at the results from this study and compared them to earlier ones about Qaroun Lake, we saw that there was more manganese (Mn), copper (Cu), and zinc (Zn) than what those previous studies found by (Elwasify, 2019) Regarding the content of organic matter in the current study, it was like those obtained by El-Zeiny et al…”
Section: Heavy Metals Distributionsmentioning
confidence: 98%